2014
DOI: 10.1387/ijdb.130351mb
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cranial placode assembly

Abstract: Cranial placodes are transient ectodermal structures contributing to the paired sensory organs and ganglia of the vertebrate head. Placode progenitors are initially spread and intermixed within a continuous embryonic territory surrounding the anterior neural plate, the so-called panplacodal region, which progressively breaks into distinct and compact placodal structures. The mechanisms driving the formation of these discrete placodes from the initial scattered distribution of their progenitors are poorly under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 74 publications
(136 reference statements)
0
9
0
Order By: Relevance
“…Precursors from the PPR segregate and coalesce into individual cranial placodes, which progressively acquire specific identities (Breau and Schneider-Maunoury, 2014; Streit, 2002; Bhat and Riley, 2011; Saint-Jeannet and Moody, 2014; McCarroll et al, 2012). Our data revealed that otic neurog1 is expressed before of what it was conceived and outside the epithelium by a group of cells that ingress during morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Precursors from the PPR segregate and coalesce into individual cranial placodes, which progressively acquire specific identities (Breau and Schneider-Maunoury, 2014; Streit, 2002; Bhat and Riley, 2011; Saint-Jeannet and Moody, 2014; McCarroll et al, 2012). Our data revealed that otic neurog1 is expressed before of what it was conceived and outside the epithelium by a group of cells that ingress during morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…After the discovery of the basic molecular cascades which determine general and/or specific cell fates (for review, see Schlosser, 2006), brand new hypotheses on the roles of cell fate changes, local sorting-out processes, and massive cell movements await further examination (Breau and Schneider-Maunoury, 2014). Other important issues still in need of clarification are the molecular regulation and the very exact functions of large-scale apoptosis first observed during the morphogenesis of placodes in Tupaia belangeri.…”
Section: Neurogenic Placodesmentioning
confidence: 99%
“…Initially, placode precursors occupy a unique territory, the pre-placodal region (PPR), where cells of different fates are interspersed (Bhattacharyya et al, 2004; Kozlowski et al, 1997; McCarroll et al, 2012; Streit, 2002; Xu et al, 2008; Pieper et al, 2011). Although it is controversial whether cell sorting segregates placode progenitors (Pieper et al, 2011), at later stages placodal cells must somehow coalesce to form spatially distinct placodes along the anterior-posterior axis (Breau and Schneider-Maunoury, 2014). In chick, DiI labelling reveals some movement of cell groups during otic, olfactory and lens placode formation (Bhattacharyya et al, 2004; Streit, 2002); while in zebrafish, cells move directionally in an integrin-α5 dependent manner as they are recruited into the otic placode (Bhat and Riley, 2011).…”
Section: Introductionmentioning
confidence: 99%